2016
DOI: 10.1117/1.oe.55.11.111605
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a variable data-rate free-space optical communication architecture using efficient coherent techniques

Abstract: Abstract. The next generation free-space optical (FSO) communications infrastructure will need to support a wide range of links from space-based terminals in low Earth orbit, geosynchronous Earth orbit, and deep space to the ground. Efficiently enabling such a diverse mission set requires an optical communications system architecture capable of providing excellent sensitivity (i.e., few photons-per-bit) while allowing reductions in data rate for increased system margin. Specifically, coherent optical transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…1) PHY/Link Cross-layer Design: Atmospheric turbulence, which results in a very slowly-varying fading, is a major degrading factor in FSO systems. As reported in [172], [173], the channel coherence time is typically 1 to 10 ms or longer, and a Gbps-transmission-rate period may cover up to thousands of consecutive frames. This quasi-static channel property makes providing reliable feedback possible, and the available CSI at the transmitter can be used to design the adaptive transmission schemes for considerable performance enhancement in FSO systems.…”
Section: B Cross-layer Framework In Fso Networkmentioning
confidence: 99%
“…1) PHY/Link Cross-layer Design: Atmospheric turbulence, which results in a very slowly-varying fading, is a major degrading factor in FSO systems. As reported in [172], [173], the channel coherence time is typically 1 to 10 ms or longer, and a Gbps-transmission-rate period may cover up to thousands of consecutive frames. This quasi-static channel property makes providing reliable feedback possible, and the available CSI at the transmitter can be used to design the adaptive transmission schemes for considerable performance enhancement in FSO systems.…”
Section: B Cross-layer Framework In Fso Networkmentioning
confidence: 99%
“…In the upper right corner both OSNR values are very high, and thus M is as low as 1, while in the lower left corner both OSNR values are very low, and thus M is as high as 5000. It is noteworthy that the maximum number of symbols that can be used for the estimation must have a total duration less than the atmospheric coherence time and laser coherence time [21]. The former is a function of the particular atmospherics and is on the order of ∼1 to 10 ms.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…In recent years flexible digital coherent receivers (DCR) widely used in optical fiber communication (OFC) systems have attracted much attention in the FSOC field because they support programmable adjustment of the sensitivity by using different data rates, modulation formats and FEC rates [4]. Recently experiments have shown that DCRs in combination with digital coherent combining (DCC) algorithms can handling FSOC signals with extremely low OSNR (much lower than 0dB) and very wide dynamic range (much large than 30 dB) [5]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, by now the performance of the Gardner's TED based TRA is investigated mainly for the OFC optical signals with OSNR around 10 dB and dynamic range less than 10 dB [13], while the FSOC DCRs need to handle optical signals with OSNR much lower than 0 dB and dynamic range much larger than 30 dB [7]. Furthermore because power consumption is more strictly limited in FSOC systems, the development of a TRA with lower computation complexity is imperative.…”
Section: Introductionmentioning
confidence: 99%